NRT1.1B improves selenium concentrations in rice grains by facilitating selenomethinone translocation. Issue 6 (9th January 2019) - Zhang, Lianhe; Hu, Bin; Deng, Kun; Gao, Xiaokai; Sun, Guoxin; Zhang, Zhengli; Li, Peng; Wang, Wei; Li, Hua; Zhang, Zhihua; Fu, Zihao; Yang, Jinyong; et al.
Summary: Selenium (Se) is an essential trace element for humans and other animals, yet approximately one billion people worldwide suffer from Se deficiency. Rice is a staple food for over half of the world's population that is a major dietary source of Se. In paddy soils, rice roots mainly take up selenite. Se speciation analysis indicated that most of the selenite absorbed by rice is predominantly transformed into selenomethinone (SeMet) and retained in roots. However, the mechanism by which SeMet is transported in plants remains largely unknown. In this study, SeMet uptake was found to be an energy‐dependent symport process involving H + transport, with neutral amino acids strongly inhibiting SeMet uptake. We further revealed that NRT1.1B, a member of rice peptide transporter (PTR) family which plays an important role in nitrate uptake and transport in rice, displays SeMet transport activity in yeast and Xenopus oocyte. The uptake rate of SeMet in the roots and its accumulation rate in the shoots of nrt1.1b mutant were significantly repressed. Conversely, the overexpression of NRT1.1B in rice significantly promoted SeMet translocation from roots to shoots, resulting in increased Se concentrations in shoots and rice grains. With vascular‐specific expression of NRT1.1B, the grain Se concentration was 1.83‐fold higher than that of wild type. These results strongly demonstrate that NRT1.1B holds great potential for the improvement of Se concentrations in grains by facilitating SeMet translocation, and the findings provide novel insight into breeding of Se‐enriched rice varieties.